Pars Terrae Labrador exhibens Sinum Davis cum regione adjacente navigata per quosdam Unitatis Fratrum : 1765 (2001)
Colour photograph of a black and white navigation chart dated 1765 showing the entrance to Davis Inlet. Colour photograph of a black and white navigation chart dated 1765 showing the entrance to Davis Inlet.